1988
DOI: 10.3171/jns.1988.68.6.0901
|View full text |Cite
|
Sign up to set email alerts
|

Significance of “ultra-early” rebleeding in subarachnoid hemorrhage

Abstract: Knowledge of the local incidence of aneurysm rupture permits the conclusion that almost every patient in the population of 933,800 persons served by the authors' institution who was stricken by this catastrophe and survived long enough to be transported was treated at this center (121 patients during 34 months). Of these, 9.1% were admitted late (greater than 72 hours after subarachnoid hemorrhage (SAH]; of the remaining cases, 94.5% were seen within 24 hours and 50% within 6 hours post-SAH. Of the 121 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…2,3,7,8,10,[12][13][14][15][16][17][18][19][20]22,23,25,35 We refer to all treatment after the first 24 hours as delayed, a group that encompassed the previously defined early, intermediate, and late timings. Eighty-eight percent of the delayed group were treated between 1 and 3 days post-ictus.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,7,8,10,[12][13][14][15][16][17][18][19][20]22,23,25,35 We refer to all treatment after the first 24 hours as delayed, a group that encompassed the previously defined early, intermediate, and late timings. Eighty-eight percent of the delayed group were treated between 1 and 3 days post-ictus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from pre-clinical and clinical studies have supported the relative safety of blood pressure reduction in acute intracerebral hemorrhage, although the benefit remains unclear [32,33]. Patients with subarachnoid hemorrhage remain at risk of second rupture acutely following an initial rupture of intracranial aneurysm [34]. The benefit of reduction of blood pressure has been linked to reduction of hemodynamic stress on aneurysm wall and prevention of second rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Hillman et al 17 reported that in 121 patients with aneurysmal SAH, rebleeding occurred before admission in 4 (3.3%) of the 11 patients with early rebleeding within 24 hours after the initial SAH. Inagawa et al 16 reported that in 418 patients with aneurysmal SAH admitted within 6 hours after the initial bleeding, rebleeding occurred before admission in 18 (4.3%) of the 61 patients with ultra-early rebleeding.…”
Section: Discussionmentioning
confidence: 99%